Quality, Stability, and Safety Data of Packed Red Cells and Plasma Processed by Gravity Separation Using a New Fully Integrated Hollow-Fibre Filter Device - T. Brune; K. Hannemann-Pohl; K. Nißle; N. Ecker; H. Garritsen (Advances in Hematology)
Background. We developed a completely closed system based on gravity separation without centrifugation steps for separation of whole blood. With this new system we compared quality and stability of the processed blood components (PRC and plasma) with respect to classical preparation. Furthermore the cost-effectiveness of this hollow fibre system was evaluated. Study Design and Methods. Whole blood collections of 15 regular blood donors were used for component preparation using the U shaped hollow fibre filter device. Results were compared to 15 whole blood preparations using centrifugation. The following parameters were evaluated: total hemoglobin, leukocyte counts, the serum concentration of total protein, lactate dehydrogenase (LDH) and potassium. Furthermore ATIII, vWF and F VIII were analyzed at different timepoints. Results. packed red cells: the data directly after separation and after 42 days of storage are in line with the guidelines of the council of Europe. Plasma. all plasma quality data are in line with the guidelines of the council of Europe for quality assurance of plasma, except for a low protein amount (factor 0.75). Conclusion. Separation of whole blood on a clinical scale in this new closed system is feasible, however the plasma protein content must be optimized.